New Antidiabetic and Free-Radical Scavenging Potential of Strictosamide in Sarcocephalus pobeguinii Ground Bark Extract via Effect-Directed Analysis - Yüce, Imanuel; Agnaniet, Huguette; Morlock, Gertrud E.; Justus Liebig University Giessen (My University, 2019)
The active principle of most traditional medicines is not known, as for Sarcocephalus pobeguinii Hua ex Pellegr. bark extract. It is used as an antidiabetic drug in Gabonese folk medicine. Diabetes mellitus is increasing globally, and products from natural sources are gaining interest as a remedy. As the active antidiabetic compounds have not been characterized so far, a mobile phase for high-performance thin-layer chromatography (HPTLC) was newly developed to target single active compounds in the unpolar ground bark extract of S. pobeguinii by effect-directed analysis (EDA). One natural compound zone showed multipotent activities by effect-directed detection, that is, antidiabetic, cholinesterase inhibiting, and antioxidative activities. Its characterization was performed via online elution of the active substance zone from the HPTLC layer into the high-resolution mass spectrometry (HRMS) system. Important parts of the structure were assigned by MS/MS experiments and led to the preliminary assignment of strictosamide, an indole alkaloid. The saccharide moiety of the active molecule was characterized with a selective derivatization reagent (diphenylamine aniline phosphoric acid reagent). Strictosamide was already reported as a constituent of the extract, and its cholinesterase inhibiting property was confirmed. However, it was newly found to be active as a free-radical scavenger and Î±-glucosidase inhibitor, which might partially explain the successful use as antidiabetic and antioxidative folk medicine. The fast bioprofiling by HPTLC-UV/vis/FLD-EDA-HRMS was proven to be suited as an analytical tool for the discovery of multipotent active compounds.
Keywords: ddc:610